2012
DOI: 10.1142/s0218488512500274
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Associative Classification Approach for Recommender Systems

Abstract: Despite the existence of different methods, including data mining techniques, available to be used in recommender systems, such systems still contain numerous limitations. They are in a constant need for personalization in order to make effective suggestions and to provide valuable information of items available. A way to reach such personalization is by means of an alternative data mining technique called classification based on association, which uses association rules in a prediction perspective. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…In a different direction, it was also detected a group of works focused on the use of fuzzy association rule mining for supporting recommendation (Table 8). Such group is composed of the researches developed by Chen and Tai [28], Pinho Lucas et al [98] [90] Model-based collaborative filtering using a fuzzy neural network to learn user's behaviours for video recommendation MAE, RMSE Netflix Video recommendation Leung et al [70], and Teng et al [122]. Specifically, Leung et al [70] introduce a collaborative filtering approach based on fuzzy association rules and multiple-level similarity.…”
Section: Maementioning
confidence: 99%
“…In a different direction, it was also detected a group of works focused on the use of fuzzy association rule mining for supporting recommendation (Table 8). Such group is composed of the researches developed by Chen and Tai [28], Pinho Lucas et al [98] [90] Model-based collaborative filtering using a fuzzy neural network to learn user's behaviours for video recommendation MAE, RMSE Netflix Video recommendation Leung et al [70], and Teng et al [122]. Specifically, Leung et al [70] introduce a collaborative filtering approach based on fuzzy association rules and multiple-level similarity.…”
Section: Maementioning
confidence: 99%
“…This type of methods has been developed more recently in order to avoid the sparsity problem (Lucas, Laurent, Moreno, & Teisseire, 2012b;Sasikala & Vidhya, 2012) that affects mainly to memory based methods, but model based ones are also affected by it. Methods within this category usually apply data mining algorithms in order to build the recommendation models, which are used to predict user preferences.…”
Section: Related Workmentioning
confidence: 99%
“…Fuzzy logic has also been successfully applied in this field in combination with associative classification (Lucas et al, 2012b). For that reason, the recommender method used in the tourism system presented in this paper is mainly based on fuzzy logic and associative classification.…”
Section: Associative Classification and Fuzzy Logicmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the cosine coefficient, convenient offers were provided to the user based on the matching degrees and the degree of pages belonging to clusters (IPACT). Lucas et al (2012) suggested a new recommender system based on fuzzy logic and associative classification. In this paper, a CBA fuzzy algorithm was used to classify users and to apply association rules.…”
Section: Related Workmentioning
confidence: 99%